(untitled) (Bioscience Journal, 2022)
The study performed a checklist of publications on species with available seed information and identified their issues and volumes. These publications occurred during the existence of the online versions of Revista Brasileira de Sementes (Brazilian Journal of Seeds) and the Journal of Seed Science. This data survey intends to represent a foundation for other studies and contribute to the knowledge of native plant species in Brazil. The search focused on the seeds of plants native to Brazil, indicating high negligence regarding the knowledge of Brazilian biodiversity because of the total number of articles published in 33 issues of Revista Brasileira de Sementes between 2002-2012 and the Journal of Seed Science, a substitute of the former journal, from 2012 to the first semester of 2020, with 28 issues published, but only 208 studies addressing seeds of plant species native to Brazil.